(3GSJNOGe GdWQb GdGMUGFjI aj JUeje GdHMK GdYdej (B/s - (3GdfYjej, eMeO YHO GdYGds; (3YfGH, YeGQ YGOd s ((3YeGf(B: s (3GdjGRhQj(B, s, 2011)
(3GdHMK GdYdej h WQb GNJjGQ GdYjfI, GNJjGQ GdaQVjGJ h JMdjd GdJHGjf , GdJUGeje GdJLQjHjI h GdebGQfGJ GdeJYOOI , GdHMK GdYdej (B: (3JUeje JGe GdJYTjI , JUeje GdbWGYGJ GdcGedI GdYThGFjI h JUeje GdeQHY GddGJjfj , JMdjd GdJHGjf GdeTJQc h CNjQG JMdjd GdJLGQH GdYGedjI (B.s
Keywords: (3GdGMUGAs; (3GdHMK GdYdejs; (3GdHMhKs